2016
DOI: 10.1182/blood.v128.22.3964.3964
|View full text |Cite
|
Sign up to set email alerts
|

A Drug-Drug Interaction Study of Ibrutinib with Moderate and Strong CYP3A Inhibitors in Patients with B-Cell Malignancy

Abstract: Background:Ibrutinib, a potent inhibitor of Bruton's tyrosine kinase, is indicated for the treatment of mantle cell lymphoma, chronic lymphocytic leukemia/small lymphocytic lymphoma (including 17p deletion), and Waldenström's macroglobulinemia. Because ibrutinib is extensively cleared by cytochrome P450 (CYP) 3A4, concomitant treatment with CYP3A inhibitors has been shown to increase ibrutinib exposure in healthy adults. However, sparse PK data from uncontrolled phase 2 studies with moderate CYP3A inhibitors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Coadministration of 140 mg ibrutinib with voriconazole demonstrated an acceptable safety profile, and the adverse event profile was consistent with the ibrutinib safety profile at therapeutic doses [6].…”
Section: Dsupporting
confidence: 58%
“…Coadministration of 140 mg ibrutinib with voriconazole demonstrated an acceptable safety profile, and the adverse event profile was consistent with the ibrutinib safety profile at therapeutic doses [6].…”
Section: Dsupporting
confidence: 58%
“…The clinical efficacy, development of resistance, and toxicity associated with SMKI treatment largely depend on the PK/ PD parameters of these compounds [60]; genetic variation in drug-metabolizing enzymes or transporters involved in the absorption, metabolism, and elimination of these SMKIs are influenced by a constellation of genetic and nongenetic factors (eg, disease, drugs, comorbid conditions, and exposures) [66,67] Net state of immunodeficiency related to aging and underlying comorbid conditions…”
Section: Pharmacogenomics and Drugdrug Interactions On Compound Metab...mentioning
confidence: 99%
“…On this basis, the concomitant administration of voriconazole and ibrutinib is currently not recommended. However, sparse PK data from uncontrolled phase 2 studies with moderate CYP3A inhibitors showed a lower magnitude of drug‐drug interactions (DDI) than observed in studies with healthy subjects or in vitro 13 . Due to its lower potential for drug‐drug‐interactions with ibrutinib, isavuconazole may be a more suitable treatment or prophylaxis option for these patients in the future 14,15 .…”
Section: Figurementioning
confidence: 99%
“…However, sparse PK data from uncontrolled phase 2 studies with moderate CYP3A inhibitors showed a lower magnitude of drug-drug interactions (DDI) than observed in studies with healthy subjects or in vitro. 13 Due to its lower potential for drug-drug-interactions with ibrutinib, isavuconazole may be a more suitable treatment or prophylaxis option for these patients in the future. 14,15 To date, isavuconazole is not established as prophylactic treatment regimen, but investigated as such in ongoing trials.…”
mentioning
confidence: 99%